Ex Glande Quercus : Bishop Griffith at the Cape : the Catholic background (1803-1837) and the first frontier 'visitation' of 1838 (Historia, 2021)
The arrival in Cape Town on Easter Saturday, April 7th, 1838 of the Irish Dominican, Patrick Raymund Griffith, titular Bishop of Palaeopolis, to minister to the Catholic community as Vicar Apostolic of the Cape of Good Hope, marked the beginning of full ecclesiastical jurisdiction by the Catholic Church in any part of present-day South Africa..Although the late Dr. W. E. Brown has examined the period of Bishop Griffith's arrival at the Cape and first expedition into the interior in so~e detail, the proJogue contributed by his editor, Michael Derrick, admIttedly provides no more than an outline of events during the earlier years of the nineteenth century.1 General histories, too, such as those by Sir George Cory, G. M. Theal and Professor Walker2 referred to in this article, while devoting some attention to the establishment and early development of the Catholic Church, deal inadequately with certain questions. Too heavy an emphasis on the part of the Catholic church historians upon documentary sources of an ecclesiastical nature and the omission of such material by the lay historians have resulted in the incomplete qr misleading treatment of such problems as the effects' of the Briti$h Catholic 'Emancipation Act of 1829 in South Africa, the general policy of the Brjtish Government with regard to the Catholic Church in the colonies and relations between the colonial government at the Cape and the Church at the time of Bishop Griffith's appointment. It is my purpose here to bring a little more light to bear upon these -points than has been shed by earlier writers, and to correct certain false impressions. My main object, however, is less the solution of specific problems than the correlation of the results of earlier research, the expan-sion of some of the material used by Dr. Brown and the presentation of certain observations from a hitherto unpublished source,s in order to examine from a fresh point of view a period of South African history when religious differences were the cause of greater friction than is the caSe today.
Keywords: Cape; Religion; Patrick Raymund Griffith; Frontier 'visitation'; Catholic; Catholic church; Bishop Griffith